Quasi-Static Mechanical Biomimetics Evaluation of Car Crash Dummy Skin - Yurun Li; Zhixin Liu; Cuiru Sun; Xiaoya Zheng; Guorui Du; Xiaoshuang Wang; Songchen Wang; Weidong Liu (Biomimetics)
Accurate replication of soft tissue properties is essential for the development of car crash test dummy skin to ensure the precision of biomechanical injury data. However, the intricacy of multi-layer soft tissue poses challenges in standardizing the development and testing of dummy skin materials to emulate soft tissue properties. This study presents a comprehensive testing and analysis of the compressive mechanical properties of both single and multi-layered soft tissues and car crash dummy skin materials, aiming to enhance the biofidelity of dummy skin. We presented one-term Ogden hyperelastic models and generalized Maxwell viscoelastic models for single-layer and multi-layer soft tissues, as well as dummy skin materials. The comparative analysis results indicate that the existing dummy skin material fails to fully consider the strain-rate-dependent characteristic of soft tissue. Furthermore, dummy skin materials exhibited ~3 times shorter relaxation times and ~2–3 times lower stress decay rates compared to soft tissues, suggesting a less viscous nature. This study provides an accurate representation of the mechanics of soft tissue and dummy skin under quasi-static compressive loading. The findings are instrumental for the development of novel bionic skin materials or structures to more precisely replicate the biomechanical properties of soft tissues, thereby enhancing the accuracy and reliability of car crash test dummies.